2023
DOI: 10.3354/meps14227
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for heterogeneous inclusion of ecosystem trends and variability in ICES fishing opportunities advice

Abstract: Incorporation of ecosystem information into fish stock assessments and management advice, a cornerstone of delivering ecosystem-based fisheries management (EBFM), occurs often implicitly, faces multiple challenges, and remains often unquantified in terms of scope and scale. This paper provides a comprehensive overview of the inclusion of ecosystem trends and variability in ICES fishing opportunities advice in the Northeast Atlantic, by covering 87% of stocks corresponding to 99% of landings. Just under 50% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Our forecasting capacities using environmentally mediated SR models, however, remain generally insufficient to improve tactical management advice (Stige et al, 2013;Subbey et al, 2014;King et al, 2015;Haltuch et al, 2019;Maunder and Thorson, 2019;Uriarte et al, 2023). Fisheries management advice in the Northeast Atlantic (NEA), for instance, showed that environmentally driven recruitment is implemented in none of the 230 studied stock assessments, and in only 11 out of 102 short-term forecasts (Trenkel et al, 2023). Tactical operational management advice therefore uses alternative approaches to account for changes in productivity (Collie et al, 2021;Silvar-Viladomiu et al, 2021;Trenkel et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our forecasting capacities using environmentally mediated SR models, however, remain generally insufficient to improve tactical management advice (Stige et al, 2013;Subbey et al, 2014;King et al, 2015;Haltuch et al, 2019;Maunder and Thorson, 2019;Uriarte et al, 2023). Fisheries management advice in the Northeast Atlantic (NEA), for instance, showed that environmentally driven recruitment is implemented in none of the 230 studied stock assessments, and in only 11 out of 102 short-term forecasts (Trenkel et al, 2023). Tactical operational management advice therefore uses alternative approaches to account for changes in productivity (Collie et al, 2021;Silvar-Viladomiu et al, 2021;Trenkel et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Fisheries management advice in the Northeast Atlantic (NEA), for instance, showed that environmentally driven recruitment is implemented in none of the 230 studied stock assessments, and in only 11 out of 102 short-term forecasts (Trenkel et al, 2023). Tactical operational management advice therefore uses alternative approaches to account for changes in productivity (Collie et al, 2021;Silvar-Viladomiu et al, 2021;Trenkel et al, 2023). These alternative approaches are required when the available data are insufficient to estimate SR models (Conn et al, 2010;Nesslage and Wilberg, 2019), but are also used in data-rich assessments by focusing on empirical methods without knowing the underlying ecological mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the risks in fisheries, it is essential to integrate climate impact knowledge into stock assessment and forecasts, to re-evaluate stock boundaries and data collection systems when mismatches arise due to a changing climate affecting stock distribution, timing of biological processes, natural mortality rates, invasive species, etc., with a dynamic monitoring and management approach (Table 2 A9). Accounting for climate change-induced effects on past trajectories of stock development is also vital for accurately incorporating these impacts in the possible explanatory variables (Trenkel et al, 2023). Additionally, offering fishing companies more flexibility regarding fishing opportunities could help safeguard against drastic changes in species availability and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…One immediate action includes accounting for the outcomes of multispecies assessments when setting fishing opportunities. The (Trenkel et al, 2023).…”
Section: Case Study 13: Coastal and Shallow Watersmentioning
confidence: 99%